2015
DOI: 10.1080/10408398.2013.765383
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Supplementation of Foods with Essential Fatty Acids—Can It Turn a Breeze without Further Ado?

Abstract: This paper focuses on the critical aspects of supplementation of foods with essential fatty acids (EFAs), the need, health benefits of supplementation and the constraints of the process. Current trend of supplementation of foods with EFAs has been gaining momentum and more research pioneers due to the health benefits in par with the direct intake of EFA supplements. Technologies including encapsulation, nanotechnology, molecular complexing, genetic engineering and more emerging means, hold promise to food supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In addition, AMPs can be used associated with nanoparticles (NPs) (Sharma et al, 2018 ). They could have several shapes and formulations (e.g., nitric oxide-releasing nanoparticles, chitosan-containing, and metal-containing nanoparticles) (Huhand and Kwon, 2011 ; Pelgrift and Friedman, 2013 ), and delivery systems, such as microencapsulation (Ganesh and Hettiarachchy, 2016 ; Kaikabo et al, 2016 ; Suresh et al, 2018 ), improving the bacterial control system. NPs can boost the effectiveness in the treatment of infectious diseases, besides protecting the peptide from degradation in the physiological environment (Rodrigues G. et al, 2019 ; Rodrigues G. R. et al, 2019 ).…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…In addition, AMPs can be used associated with nanoparticles (NPs) (Sharma et al, 2018 ). They could have several shapes and formulations (e.g., nitric oxide-releasing nanoparticles, chitosan-containing, and metal-containing nanoparticles) (Huhand and Kwon, 2011 ; Pelgrift and Friedman, 2013 ), and delivery systems, such as microencapsulation (Ganesh and Hettiarachchy, 2016 ; Kaikabo et al, 2016 ; Suresh et al, 2018 ), improving the bacterial control system. NPs can boost the effectiveness in the treatment of infectious diseases, besides protecting the peptide from degradation in the physiological environment (Rodrigues G. et al, 2019 ; Rodrigues G. R. et al, 2019 ).…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…Net rearing system ducks in current study exhibited the escalated ƩMUFA, ƩMUFA/ƩSFA, and the increasing trend of ƩSFA extensively, implying a positive impact of NRS on meat flavor improvement. Current study also showed fatty acids including C20:5(n-3), C20:4(n-6), C22:6(n-3), C18:2(n-6)c, C18:3(n-3), and C20:3(n-6) were higher in NRS ducks, among which C18:2(n-6)c, C18:3(n-3), and C20:4(n-6) were essential fatty acids ( Dal Bosco et al., 2016 ), C18:2(n-6)c and C18:3(n-3) were also important substrates for the synthesis of n-6 and n-3 long chain-polyunsaturated fatty acids ( LC-PUFA ), including C22:5(n-3), C20:5(n-3), and C22:6(n-3) ( Ganesh and Hettiarachchy, 2016 ). This finding indicated NRS ducks might have better absorption of essential fatty acids and less fatty acids utilization than FRS ducks, which may result from the fewer exercise ducks would take in NRS, because physical exercise results in fatty acids oxidation in muscles ( Musi et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…1). DHA is crucial to visual acuity and neural development and is the most abundant ω-3 fatty acid in the brain and retina of mammals1320212223242526. DHA also modulates the carrier-mediated transport of choline, glycine, and taurine27, the latter being crucial to neuronal development28.…”
Section: Discussionmentioning
confidence: 99%